Test the Solving of Seed Skin and Media Type Against Germination of Pumpkin Seeds (Cucurbita Maschata) - Sri Hidayati; Sri Purwanti (Faculty of Agriculture, Merdeka University Surabaya, 2018)
Objectives of the research are (1) to test various treatments of seed skin breakdown and media types to pumpkin germination (2) to test various treatments splitting of seed skin on pumpkin germination, (3) To test various types of media treatments for pumpkin germination. Factorial research methods in Randomized Block Design (RBD), consisting of two factors, namely: Treatment of seed skin breakdown with 2 levels of treatment and treatment of media types with 4 levels of treatment. Each treatment combination was repeated three times and each treatment combination consisted of 20 pumpkin seeds. The first factor is the treatment of seed skin breakdown consisting of P0 : without breaking the seed skin and P1 : Breaking the seed skin. While the second factor is media type treatment consisting of M1: Merang paper; M2: Garden Land; M3: Sand and M4 : Fertilizer Cage. Observations carried out consisted of germination rate, germination percentage, plumula length and radicle length. The results of the study and discussion, can be concluded as follows: Overall the combination of the treatment of seed skin breakdown and the type of media on gourd seeds germination has not given a significant interaction effect, except for the significant growth of radicle length. no significant effect on the length of the radicles and the length of pumpkin plumula, very significant effect on germination rate, and on the percentage of germination significantly. In the treatment of the type of media it has a very real effect on all observation parameters. The combination of the treatment of seed skin cracking and paper planting media (P1M1) gave the highest yield on the average length of radicles, germination on the paper medium (M1) gave the longest length of the radicle, the fastest germination rate, and the highest germination percentage obtained at skin stripping treatment (P1).